Gymnastic training and bone density in pre-adolescent females - Dyson, K.; Blimkie, C. J.; Davison, K. S.; Webber, C. E.; Adachi, J. D. (Medicine & Science in Sports & Exercise, 1997)
Bone mineral density (BMD) was compared between 7-11-yr-old female gymnasts (GYM: N = 16) with a history of high volume impact loading (minimum of 15 h.wk-1 for past 2 yr) and healthy nonathletic controls (CON: N = 16). Whole body (WB) and regional areal BMD measures were determined by dual energy x-ray absorptiometry (DXA) normalized for height and body mass and also converted to bone mineral apparent density (BMAD). Volumetric BMD and bone cross-sectional areas were also measured by peripheral QCT (pQCT) at the left distal radius. GYM were significantly (P < 0.01) shorter (129.3 +/- 5.7 vs 136.7 +/- 4.4 cm; means +/- SD) and leaner (15.1 +/- 1.9 vs 19.6 +/- 4.3% body fat from DXA), and had significantly (P < 0.05) greater femoral neck (0.698 +/- 0.058 vs 0.648 +/- 0.064 g.cm-2) and trochanter (0.616 +/- 0.060 vs 0.530 +/- 0.084 g.cm-2) areal BMD than CON. GYM also had significantly higher whole body (0.101 +/- 0.009 vs 0.094 +/- 0.007 g.cm-3), femoral neck (0.245 +/- 0.060 vs 0.205 +/- 0.049 g.cm-3) and lumbar spine (0.227 +/- 0.014 vs 0.210 +/- 0.026 g.cm-3) BMAD compared with CON. Height normalized areal BMD measures were also significantly higher at all sites in GYM. Radial total (367.7 +/- 51.6 vs 307.4 +/- 27.6 mg.cm-3), trabecular (207.9 +/- 45.3 vs 163.8 +/- 31.4 mg.cm-3), and cortical (496.9 +/- 67.5 vs 429.8 +/- 33.8 mg.cm-3) BMD were also significantly greater in the GYM compared with the CON. In conclusion, high volume impact loading was associated with greater (compared with controls) whole body and regional bone mineral density in pre-adolescent female gymnasts.